Analysis of thermal-hydraulic performance and flow structures of nanofluids across various corrugated channels: An experimental and numerical study - Ajeel R.K.; Saiful-Islam W.; Sopian K.; Yusoff M.Z. (Elsevier Ltd, 2023)
Alumina; Aluminum oxide; Channel flow; Flow structure; Heat flux; Heat transfer performance; Kinetic energy; Kinetics; Reynolds number; Silica; Volume fraction; Empirical correlations; Experimental and numerical studies; Heat transfer and pressure drop; Heat-transfer ratios; Heating and cooling systems; Thermal-hydraulic performance; Turbulent kinetic energy; Turbulent viscosity; Nanofluidics